Is the persistence of teacher effects in early grades larger for lower-performing students? - Spyros Konstantopoulos; Min Sun (Institute for the Study of Labor (IZA), 2011)
We examined the persistence of teacher effects from grade to grade on lower-performing students using high-quality experimental data from Project STAR, where students and teachers were assigned randomly to classrooms of different sizes. The data included information about mathematics and reading scores and student demographics such as gender, race, and SES. Teacher effects were computed as residual classroom achievement within schools and within grades. Then, teacher effects were used as predictors of achievement in following grades and quantile regression was used to estimate their persistence. Results consistently indicated that all students benefited similarly from teachers. Overall, systematic differential teacher effects were not observed and it appears that lower-performing students benefit as much as other students from teachers. In fourth grade there was some evidence that lower-performing students benefit more from effective teachers. Results from longitudinal analyses suggested that having effective teachers in successive grades is beneficial to all students and to lower-performing students in particular in mathematics. However, having low-effective teachers in successive grades is detrimental to all students and to lower-performing students in particular in reading.
urn:nbn:de:101:1-201110102264
Keywords: I20; 330; teacher effects; low-achievers; quantile regression; Bildungsniveau; Kinder; Geschlecht; Ethnische Gruppe; Personalbeurteilung; USA